Interaction of α Carboxyl Terminus 1 Peptide With the Connexin 43 Carboxyl Terminus Preserves Left Ventricular Function After Ischemia‐Reperfusion Injury. Issue 16 (20th August 2019) - Jiang, Jingbo; Hoagland, Daniel; Palatinus, Joseph A.; He, Huamei; Iyyathurai, Jegan; Jourdan, L. Jane; Bultynck, Geert; Wang, Zhen; Zhang, Zhiwei; Schey, Kevin; Poelzing, Steven; McGowan, Francis X.; et al.
Abstract : Background: α Carboxyl terminus 1 (αCT1) is a 25–amino acid therapeutic peptide incorporating the zonula occludens‐1 (ZO‐1)–binding domain of connexin 43 (Cx43) that is currently in phase 3 clinical testing on chronic wounds. In mice, we reported that αCT1 reduced arrhythmias after cardiac injury, accompanied by increases in protein kinase Cε phosphorylation of Cx43 at serine 368. Herein, we characterize detailed molecular mode of action of αCT1 in mitigating cardiac ischemia‐reperfusion injury. Methods and Results: To study αCT1‐mediated increases in phosphorylation of Cx43 at serine 368, we undertook mass spectrometry of protein kinase Cε phosphorylation assay reactants. This indicated potential interaction between negatively charged residues in the αCT1 Asp‐Asp‐Leu‐Glu‐Iso sequence and lysines (Lys345, Lys346) in an α‐helical sequence (helix 2) within the Cx43‐CT. In silico modeling provided further support for this interaction, indicating that αCT1 may interact with both Cx43 and ZO‐1. Using surface plasmon resonance, thermal shift, and phosphorylation assays, we characterized a series of αCT1 variants, identifying peptides that interacted with either ZO‐1–postsynaptic density‐95/disks large/zonula occludens‐1 2 or Cx43‐CT, but with limited or no ability to bind both molecules. Only peptides competent to interact with Cx43‐CT, but not ZO‐1–postsynaptic density‐95/disks large/zonula occludens‐1 2 alone, prompted increased pS368 phosphorylation. Moreover, in an ex vivo mouse model of ischemia‐reperfusion injury, preischemic infusion only with those peptides competent to bind Cx43 preserved ventricular function after ischemia‐reperfusion. Interestingly, a short 9–amino acid variant of αCT1 (αCT11) demonstrated potent cardioprotective effects when infused either before or after ischemic injury. Conclusions: Interaction of αCT1 with the Cx43, but not ZO‐1, is correlated with cardioprotection. Pharmacophores targeting Cx43‐CT could provide a translational approach to preserving heart function after ischemic injury.